Cultura de segurança do paciente: um retrato das Unidades de Terapia Intensiva do Estado de Alagoas - Martins, Nathália Medeiros (2018)
This study aims at the perception of the safety culture of the patient by the nursing professionals who work in the General Intensive Care Units of the Alagoas hospitals. A quantitative, exploratory descriptive and cross - sectional study of the Survey type, whose general objective was to evaluate the perception of the safety culture of the professionals of the nursing team working in the General Intensive Care Units of Alagoas. It was carried out in all the hospital institutions of Alagoas that have general Intensive Care Units listed in the National Register of Health Establishments and that had at least two years of operation, totaling sixteen who agreed to participate in the research. The instruments used for research were the Safety Attitudes Questionnaire and an additional information questionnaire developed by the researcher. The population was composed of all the nursing professionals (nurses, technicians and nursing assistants) who were in the exercise of their work activities in the Intensive Care Units of the participating hospitals. Of the 534 professionals who were effectively part of the work scales during the data collection period, 346 accepted to participate in the study and 339 were part of the study. Participants in this research were predominantly female (74.93%) (n = 254) and the majority were nursing technicians (72.27%) (n = 245). It was found that in private hospitals the average number of patients per professional is higher. Therefore, in relation to the Safety Attitudes Questionnaire. the domain that presented the highest average was related to satisfaction with the work, and the lowest average was the one referring to the item without domain of communication failures. It was possible to verify that in all domains the scores of the private hospitals were higher in relation to the public hospitals, except in the management perception that the opposite occurred. It was verified that the nursing professionals who work in the Intensive Care Units of the State of Alagoas present weakened patient safety attitudes related to most of the domains of the Safety Attitudes Questionnaire, the communication failures appear as a problem in the reality of the Units of Intensive Care and Alagoas seem to be one of the great barriers among professionals for establishing a safe care. it is essential that risk managers, nursing professionals responsible for the Intensive Care Units know the reality of their units, so that measures can be established to establish the patient's safety culture. The first step is to evaluate what culture exists in them and from there to work these critical "nodes", some of those cited above, to establish a safe, integral nursing care centered on the needs of the individual and their right to receive a scheduled assistance from SP.